(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The principle of lexical economy describes how language users minimize cognitive and articulatory effort while maximizing communicative efficiency. Abbreviations serve as a salient manifestation of this principle in contemporary discourse, facilitating brevity, ease of production, and rapid comprehension across formal and informal contexts. This study investigates how different types of abbreviations contribute to lexical economy and how they are distributed across registers of language use.